Productivity and Profitability of Tomato (Lycopersicum esculentum M.) Production in Masbate Under Improved Nutrient Management with and without Mulching - Velza, Jacob Frederick P.; Valler, Donata L.; Loraña, John L.; Alcantara, Edwin L.; Ibañez, Roger Y. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Field trial on tomato production was conducted under two sources of fertilizer through integrated application with and without mulching material to measure the growth, productivity and profitability of the said crop in the province of Masbate. The study was laid in a two-factor factorial Randomized Complete Block Design. Fertilizer treatments were tested in treatment of mulching (rice straw and control). The factorial treatment combinations were as follows: A1B1 - no fertilizer and without mulching; A2B1 - complete fertilizer without mulching; A3B1 - goat manure without mulching; A4B1 - complete fertilizer + goat manure without mulching; A1B2 - no fertilizer and with mulching; A2B2 - complete fertilizer with mulching; A3B2 - goat manure with mulching; A4B2 - complete fertilizer + goat manure with mulching. The study revealed that the treatment that exhibits higher growth (plant height and number of branches) and yield (38.41 t/ha.) is in the treatment under complete fertilizer + goat manure. The same treatment also obtained higher number of fruits (543) and higher number of marketable fruits (424) per treatment with significant difference. In terms of the fruit size, length and diameter of the tomato, complete fertilizer + goat manure shows dominant effect. Profitability showed significant difference between treatments were the complete fertilizer + goat manure, complete fertilizer, goat manure, and control got 1,334, 1,265.15, 517.51 and 52.20 respectively. Therefore, the integration of organic (goat manure) and synthetic fertilizer (Triple 14) will enhance the yield of the tomato in Masbate and it is highly profitable.